Economic Valuation of Mangrove Ecosystem in Coastal Area of Rokan Hilir Regency, Riau Province - Trisla Warningsih; Kusai Kusai; Zulkarnain Zulkarnain; Lamun Bathara; Isma Mulyani; Devia Sari (Faculty of Fisheries and Marine Science, Brawijaya University, 2020)
Mangrove ecosystem is a very important resource for the continuity of community life in coastal areas. Mangrove ecosystem in the coastal area of downstream Rokan district has decreased mangrove area because it is used as a pond area to reduce the production of mangrove litter as an ecological function that can be a carrying capacity of coastal capture fisheries. However, the use of coastal areas as pond areas provides economic benefits for aquaculture. This study aims to calculate the economic value of the Rokan Hilir Coastal mangrove ecosystem. This research was conducted in March-April 2019 in the survey method. Analysis to calculate the total economic value of the mangrove ecosystem is NET=ML+MTL+MP. The results showed the total economic benefit value of Rokan Hilir mangrove forest reached IDR 98.697.950.594 / year was a direct benefit value of IDR 701,425,106 / year, indirect benefits were obtained at IDR 94,606,056,000 / year, and the optional benefits reached IDR 3,512,126,520 / year. Mangrove ecosystems are ecosystems that provide many benefits to the Rokan Hilir Coastal community, so this ecosystem is highly expected to be sustainable.